EFEKTIVITAS PENGGUNAAN MICROSOFT TEAMS DALAM PEMBELAJARAN DARING - Fasilatul Hikmah (Universitas Tribhuwana Tunggadewi, 2021)
This study aims to determine the effectiveness of using the Microsoft Teams application during online learning for third grade students at SDN Simokerto VI/139 Surabaya. Microsof t Teams was an application that has been used as an online learning medium during the COVID-19 pandemic. The research method that has been used wass descriptive qualitative. Researchers collected data and then described respondents' answers about using the Microsoft Teams application. The research instrument used was a questionnaire and observation. The results showed that 29 students or 93% stated that it was easier to use Microsoft Teams in online learning. Microsoft Teams is also easily accessible to students during lessons. Through Microsoft Teams, it becomes easy for students to learn with easy access, and helps students learn during online learning. In addition, students more easily understand the material presented by the teacher so that it has an impact on good student learning outcomes. Students are more enthusiastic about learning because they can communicate with teachers and friends even though they are not face to face